The Urgency of Regional Regulation Bill of Serdang Bedagai Regency on Trading Business - Ramlan Ramlan; Eka NAM Sihombing; Fajriawati Fajriawati (Randwick International of Social Science Journal, 2020)
This study aims to discuss the urgency of regional regulation bill of serdang bedagai regency on trading business. Various problems regulated in this regulation include: The quality that is owned between modern retail and traditional retail is not comparable in terms of capital, management to human resources; The increasing number of modern retailers has made it difficult for traditional retailers to develop because they have to deal directly with modern retailers with better quality; There are no strict sanctions against retailers who violate the relevant provisions; Unilateral determination of the types, sizes and prices of trading terms to retail; and The incomplete application of regulations and criminal provisions whose content is not yet optimal. Currently, the gap between modern trading businesses and traditional trading businesses lies in the distribution chain that is digitally integrated in modern trading businesses, creating synergies among its users. Meanwhile, traditional trading business entrepreneurs are usually cash based and have limited integration with suppliers or banks to manage purchases, supplies and payments. Based on this condition, it is very necessary to form a regulation to create a balanced competition between traditional trading businesses and modern trading businesses, regulations that are able to bring justice to all entrepreneurs, not only provide protection for traditional trading businesses and forget about modern trading businesses that also have a very positive impact on the existence of the regional and national economy or vice versa. The regulation is in the form of a Trade Business Regional Regulation. Regional Regulation Bill of Serdang Bedagai Regency on Trading Business